PENGARUH INTERVENSI EDUKASI BERBASIS APLIKASI PONSEL PINTAR TERHADAP TINGKAT KUALITAS HIDUP PENDERITA DIABETES MELITUS TIPE 2 - Juhaeni, Ameirzan Maulana; Ghozali, Muhammad Thesa (As-Syifaa Jurnal Farmasi, 2023)
Poor quality of life is one of the leading causes of death in individuals with diabetes mellitus, so people with diabetes need to be educated about the disease to have a decent quality of life and avoid complications. Today's technological advances have resulted in the emergence of many new innovations, including in the health sector, such as the use of smartphone apps for patient education. This study seeks to describe the quality of life of type 2 diabetes mellitus patients in the outpatient installation at PKU Muhammadiyah Gamping Hospital and to ascertain whether there are any differences between the quality of life of these patientss' prior to and following the administration of educational interventions based on smartphone applications. This study falls under the category of pre-experimental research, with a one-group pretest and posttest design. Respondents for this study were recruited using the quota sampling approach, which yielded up to 50 participants based on the research requirements. This study was conducted at the PKU Muhammadiyah Gamping Hospital outpatient facility from October to December 2022. The Diabetes Quality of Life (DQoL) questionnaire was used to collect research data before and after the smartphone application-based educational intervention "Diary Diabetes" was given to respondents. According to the findings of this study's descriptive statistical analysis, out of 50 respondents, 37 (or 74%) had high levels of life satisfaction. The study's findings also revealed an increase in the average, median, maximum, and standard deviation of the respondents. According to the hypothesis test, the study's paired sample t- test had a significance value of 0.003, indicating that there was a difference between the patients' quality of life before and after receiving smartphone application-based educational interventions for type 2 diabetes mellitus in the outpatient facility of PKU Muhammadiyah Gamping Hospital